Effectiveness of knowledge and skills after online simulation interventions and blended learning are given - Reghula Maryeti Sandra; Ahsan Ahsan; Laily Yuliatun (Universitas Aisyah Pringsewu, 2023)
In the 4.0 industrial revolution era, clinical learning has been developed through online learning and blended learning. There needs to be an analysis of the effectiveness of this learning method on nursing students. This study aimed To determine the effectiveness of online and blended method training in improving knowledge and skills of Cardiopulmonary Resuscitation (CPR) in nursing students. The study design of this study is quasi experimental, where the groups are non-randomized into group A and group B, and selected randomly. The educational intervention included a theoretical session on CPR and a demonstration plus hands-on practice. Nurses' knowledge was measured using a self-administered questionnaire pre- and post-intervention, and a checklist form for assessing skills. Data were analyzed using repeated measure analysis univariate, bivariate and multivariate analysis. The results showed that the knowledge score in group A was 1.35±0.93 which was higher than the increase in the knowledge score in group B of 1.15±0.93. And skills in group A of 3.70±2.67 are lower than the increase in the skill score of group B of 5.00±1.89. Obtained a p-value greater than 5% (0.228 more than 0.050) indicating that simultaneously there was an insignificant difference between the 2. It can be concluded that both methods are equally effective in increasing the variable scores.